Analisis Tingkat Kenyamanan Termal dan Kepuasan Pengguna di Laboratorium Teknik Mesin Universitas Malikussaleh - Helfialna, Fahdea; Safyan, Adi; Olivia, Sisca (Rifa'Institute, 2023)
The laboratory is a place used for practicum, research, and can support the teaching and learning process. The mechanical engineering laboratory space is the most important space and is often used to support study activities in the mechanical engineering department of the university. However, laboratory conditions that do not use air conditioning and only rely on natural ventilation result in the lack of thermal comfort for users to comfortably support user activities. Apart from that, the high temperatures produced by heat through metal roofs from exposure to sunlight, equipment machines that emit hot temperatures, as well as the small amount of incoming and outgoing air flow are the objectives of selecting objects in this research. Thermal comfort is influenced by several variables, namely external, internal factors and air opening design. This research uses a mix method, namely qualitative and quantitative research methods with a descriptive approach. The results of this research are in the form of an analysis which shows that the thermal conditions of the four laboratory rooms do not meet the thermal comfort standards set by ASHRAE with conditions being above the comfort zone and the PMV comfort index cannot be said to be comfortable because there is no wind blowing into the building.